2013
DOI: 10.5897/jdae12.165
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of New Rice for Africa (NERICA) technology in Ogun State, Nigeria

Abstract: This study was carried out with the aim to find out the level and socio-economic determinants of the adoption of New Rice for Africa (NERICA) using Ewekoro Local Government Area of Ogun State in Nigeria as a case study. One hundred and sixteen rice farmers were randomly selected in this area, twenty eight of which adopted NERICA rice varieties within 2009/2010 cropping season. Information was gathered through the use of well structured questionnaire and personal interview of the farmers. Descriptive statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Table 7 revealed that pest (birds and rodents) infestations ( x = 1.92), climate change ( x = 1.59) and inadequate capital for adopting the innovation ( x = 1.51) were ranked as most challenging constraints limiting the adoption of the NERICA rice variety in the study area. This finding sup- ports the report given by [1], who also stated that pest infestation and inadequate funds as major constraints mitigating rice production. The problem of pest infestation has made the rice farmers to have sleepless nights particularly during rice-flowering period till maturity time when the birds as the major pest are infesting at an alarming rate.…”
Section: Constraints In Adopting Nerica Rice Varietysupporting
confidence: 63%
“…Table 7 revealed that pest (birds and rodents) infestations ( x = 1.92), climate change ( x = 1.59) and inadequate capital for adopting the innovation ( x = 1.51) were ranked as most challenging constraints limiting the adoption of the NERICA rice variety in the study area. This finding sup- ports the report given by [1], who also stated that pest infestation and inadequate funds as major constraints mitigating rice production. The problem of pest infestation has made the rice farmers to have sleepless nights particularly during rice-flowering period till maturity time when the birds as the major pest are infesting at an alarming rate.…”
Section: Constraints In Adopting Nerica Rice Varietysupporting
confidence: 63%